1998
DOI: 10.1086/316252
|View full text |Cite
|
Sign up to set email alerts
|

Superhumps in Cataclysmic Binaries. XV. EG Cancri, King of the Echo Outbursts

Abstract: We report photometry and spectroscopy of the dwarf nova EG Cancri in its 1996/1997 episode of eruptions. The main eruption was clearly a superoutburst featuring common superhumps with a period of 0.06036(2) days, establishing the star as a new member of the SU UMa class of dwarf novae. At the end of the main eruption, the superhumps were replaced by another wave of slightly longer period (0.06045 days), which endured for at least another 90 days. The properties of the latter wave suggest identification as a "l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 25 publications
11
54
1
Order By: Relevance
“…This is in general agreement with the previous observations of other WZ Sge-type objects (see Patterson et al 1998;Kato et al 2008;Kato 2015, and references therein), although in SSS J122222 these late superhumps were seen for significantly longer time than in any other WZ Sge-type system. Moreover, the stable modulations still persisted even about 420 d after the superoutburst, but their period has further increased by about 2 per cent.…”
Section: Late Superhumpssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in general agreement with the previous observations of other WZ Sge-type objects (see Patterson et al 1998;Kato et al 2008;Kato 2015, and references therein), although in SSS J122222 these late superhumps were seen for significantly longer time than in any other WZ Sge-type system. Moreover, the stable modulations still persisted even about 420 d after the superoutburst, but their period has further increased by about 2 per cent.…”
Section: Late Superhumpssupporting
confidence: 93%
“…For example, a similarly strong cool continuum source was reported for EG Cnc by Patterson et al (1998), which also showed the red colours (B-I ≃ 1.4). However, multicolour observations after the active stage of superoutbursts are rare and sporadic, and no detailed study of the above phenomenon has ever been presented.…”
Section: Long-term Light Curve and The Colour Evolutionsupporting
confidence: 57%
See 1 more Smart Citation
“…a few percent longer than P orb ), but have phases of ∼0.5 different from those of ordinary superhumps. Since this signal was observed long after then cessation of the 1999 outburst, Woudt & Warner (2001) suggested that V359 Cen may have shown a long persistence of late superhumps as was observed in a WZ Sge-type dwarf nova in EG Cnc Patterson et al 1998). …”
Section: Super-qposmentioning
confidence: 81%
“…The 1996 superoutburst of the WZ Sge-type object EG Cnc also showed multiple rebrightenings [20], [19] (see figure 2). As you can see, the rebrightenings of ASASSN-14ei are very similar to ones of EG Cnc except the time scale.…”
Section: Wz Sge-like Rebrighteningsmentioning
confidence: 98%